Pharmacotherapy of Vestibular Disorders and Nystagmus - Strupp, Michael; Kremmyda, Olympia; Brandt, Thomas (Seminars in Neurology, 2013)
Vertigo and dizziness are with a life-time prevalence of ∼30% among the most common symptoms and are often associated with nystagmus or other oculomotor disorders. The prerequisite for a successful treatment is a precise diagnosis of the underlying disorder. In this overview, the current pharmacological treatment options for peripheral and central vestibular, cerebellar, and oculomotor disorders including nystagmus are described. There are basically seven groups of drugs that can be used (the “7 As”): antiemetics; anti-inflammatory, anti-Menière's, and antimigraine medications; antidepressants, anticonvulsants, and aminopyridines. In acute vestibular neuritis, recovery of the peripheral vestibular function can be improved by treatment with oral corticosteroids. In Menière's disease, a long-term high-dose treatment with betahistine-dihydrochloride (at least 48 mg three times daily) had a significant effect on the frequency of the attacks; the underlying mode of action is evidently an increase in inner-ear blood flow. The use of aminopyridines is a well-established therapeutic principle in the treatment of downbeat and upbeat nystagmus as well as episodic ataxia type 2 and cerebellar gait disorders. As was shown in animal experiments, these potassium channel blockers increase the activity and excitability and normalize irregular firing of cerebellar Purkinje cells. They evidently augment the inhibitory influence of these cells on vestibular and deep cerebellar nuclei. A few studies showed that baclofen improves periodic alternating nystagmus; gabapentin and memantine improve pendular and infantile nystagmus. However, many other eye-movement disorders such as ocular flutter, opsoclonus, central positioning, and see-saw nystagmus are still difficult to treat. Although substantial progress has been made, further state-of-the-art trials must still be performed on many vestibular and oculomotor disorders, namely Menière's disease, vestibular paroxysmia, vestibular migraine, and many forms of central eye-movement disorders.
Keywords: vestibular neuritis; Menière's disease; vestibular paroxysmia; vestibular migraine; episodic ataxia type 2; downbeat nystagmus; upbeat nystagmus